2008
DOI: 10.1371/journal.pone.0002489
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of HIV on the Sensitivity of a Whole Blood IFN-γ Release Assay in Zambian Adults with Active Tuberculosis

Abstract: BackgroundInterferon gamma release assays (IGRA) are replacing the tuberculin skin test (TST) as a diagnostic tool for Mycobacterium tuberculosis infection. However research into the test's performance in the high HIV-TB burden setting is scarce. This study aimed to define the sensitivity of an IGRA, QuantiFERON-TB® Gold In-Tube (QGIT), in adult Zambian patients with active smear-positive tuberculosis. Secondary outcomes focussed on the effect of HIV on the test's performance.Principal FindingsPatients attendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
96
6
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 22 publications
16
96
6
2
Order By: Relevance
“…It is likely that using the definite-TBM group in the analysis may overestimate sensitivity while using the definite plus the probable group may underestimate sensitivity. The true performance probably lies somewhere in between (39).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that using the definite-TBM group in the analysis may overestimate sensitivity while using the definite plus the probable group may underestimate sensitivity. The true performance probably lies somewhere in between (39).…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have shown that the IGRAs, in particular the QFT-IT, render many indeterminate and possibly also false-negative results in HIV-infected individuals with a low CD4 cell count [13,14,[65][66][67][68][69][70][71][72]. Therefore, alternative approaches in this group of patients are necessary, but only few studies have evaluated IP-10 for this purpose.…”
Section: Hiv-infected Individualsmentioning
confidence: 99%
“…58 In 4 studies that compared performance of QFT-IT in HIV-infected and non-infected adults with active TB, mean sensitivity was 64% in HIV-infected patients and 79% in non-HIV-infected patients. [59][60][61][62] Although the overall sensitivity of T-SPOT.TB is higher than that of QFT-IT in otherwise healthy people, data from head-to-head comparisons in HIV-infected patients are scarce. 60,63,64 In three studies, covering a total of 39 patients with culture-confirmed TB, QFT-IT and T-SPOT.TB detected 74% and 82% of cases respectively.…”
Section: Interferon-γ-based Assays For Diagnosing Active Tuberculosismentioning
confidence: 99%
“…60,64 Despite impaired sensitivity, IFN-γ-based tests are clearly superior to TST for the diagnosis of active TB in these patients. 61, [65][66][67] IFN-γ-based tests may be of value in diagnosing TB in childhood, due to the absence of microbiological confirmation in a high proportion of cases. In a large prospective study, the sensitivity of T-SPOT.TB was 83%, and was not affected by HIV status.…”
Section: Interferon-γ-based Assays For Diagnosing Active Tuberculosismentioning
confidence: 99%